Recalled parental rearing behavior shapes mental health after preterm birth: Evidence from the Gutenberg Prematurity Study - Ernst, Mareike; Schuster, Alexander K.; Mildenberger, Eva; Otten, Daniëlle; Brähler, Elmar; Tesarz, Jonas; Urschitz, Michael Siegfried; Pfeiffer, Norbert; Beutel, Manfred; Fieß, Achim (Psychiatry research, 2023)
Associations of preterm birth with later-life mental distress are well-established. A research gap concerns the role of psychosocial factors such as the family context. This study investigated associations of recalled parental rearing behavior with both preterm birth characteristics and psychological symptom burden later in life. Based on birth registry data of the Mainz University Hospital in Germany (infants born between 1969 and 2002) and using a selection algorithm, a cohort study comprising four gestational age (GA) strata was conducted (≥ 37 weeks: n = 138; 33-36 weeks: n = 132; 29-32 weeks: n = 106; ≤ 28 weeks: n = 132). Participants underwent a medical examination and completed standardized questionnaires. We investigated differences in dimensions of recalled parental rearing behavior according to GA and tested pre-/perinatal stress indicators and recalled parental rearing behavior as statistical predictors of depression and anxiety symptoms later in life. Lower GA was associated with more recalled emotional warmth and overprotection. Recalled emotional warmth was associated with fewer depression and anxiety symptoms, while recalled overprotection co-occurred with more depression symptoms. The findings indicate the relevance of parental rearing behavior for the offspring's mental health. As preterm birth implicates stress for the whole family requiring adaptive parental behavior, the latter could be an important modifiable risk factor.